2021
DOI: 10.1126/sciadv.abe4459
|View full text |Cite
|
Sign up to set email alerts
|

Martian subsurface cryosalt expansion and collapse as trigger for landslides

Abstract: On Mars, seasonal martian flow features known as recurring slope lineae (RSL) are prevalent on sun-facing slopes and are associated with salts. On Earth, subsurface interactions of gypsum with chlorides and oxychlorine salts wreak havoc: instigating sinkholes, cave collapse, debris flows, and upheave. Here, we illustrate (i) the disruptive potential of sulfate-chloride reactions in laboratory soil crust experiments, (ii) the formation of thin films of mixed ice-liquid water “slush” at −40° to −20°C on salty Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 147 publications
1
22
0
Order By: Relevance
“…Most of the ridges have collapsed, which suggests loss of structural integrity and eroded to axial deposits of intraclastic selenite detritus and regolith (Figure 4). It is possible that this collapse is linked to climate-related, watertable-elevation cycles, which caused dissolution of salt or hydration and dehydration of mixed chloride-sulfate salts in the subsurface (Bishop et al, 2021) that led to volume changes and destabilization of the surface (Figure 9). This would lead to linear features creating quasi-tiles, such as, PolygonRidges and Megapolygons.…”
Section: Origin and Evolution Of Surface Forms-the Role Of Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the ridges have collapsed, which suggests loss of structural integrity and eroded to axial deposits of intraclastic selenite detritus and regolith (Figure 4). It is possible that this collapse is linked to climate-related, watertable-elevation cycles, which caused dissolution of salt or hydration and dehydration of mixed chloride-sulfate salts in the subsurface (Bishop et al, 2021) that led to volume changes and destabilization of the surface (Figure 9). This would lead to linear features creating quasi-tiles, such as, PolygonRidges and Megapolygons.…”
Section: Origin and Evolution Of Surface Forms-the Role Of Watermentioning
confidence: 99%
“…An alternative explanation for ridges on Mars may be destabilization of hydrated salts in the subsurface. Bishop et al (2021) proposed such a model for recurring slope lineae (RSL). In their model, RSL occur as a consequence of seasonal hydration and dehydration of subsurface chloride-sulfate salts leading to slope failure.…”
Section: Implications For Mars Explorationmentioning
confidence: 99%
“…Surface frost (CO 2 and H 2 O) forms in only some RSL source regions and will sublimate before RSL typically become active (Schorghofer et al., 2019). Other hypotheses are that mass wasting may occur when damp surface materials dehydrate (Schorghofer et al., 2002; Shoji et al., 2020) or when subsurface brines cause uplift or collapse (Bishop et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The same type of landslide observed on impact crater slopes was also attributed to thermal-stress (Tesson et al, 2020). Recently, Bishop et al (2021) suggested that the occurrence of Martian landslides could be related to the subsurface cryosalt expansion. They used analogue field investigations on Earth and laboratory experiments to demonstrate that when salts interact with gypsum or water underground, it can cause disruptions on the surface, and may trigger collapses and landslides.…”
Section: Introductionmentioning
confidence: 73%